Streptococcus pneumoniae isolated during 2002-2006: serotypes and antibiotics resistance. Correlation with existing vaccines - Guevara-Duncan, José María (2008)
Objectives: To identify isolated S. pneumoniae serotypes correlating them with those covered by existing vaccines and determining antimicrobial resistance. Design: Descriptive, observational and longitudinal study. Setting: Daniel A Carrion Tropical Medicine Institute, School of Medicine, UNMSM. Biologic material: Streptococcus pneumoniae stocks. Interventions: Forty Streptococcus pneumoniae stocks isolated between 2002 and 2006 were serotyped at Carlos III Health Institute in Madrid, Spain; 15 were invasive, 11 isolated from localized infections, 6 from carriers and 8 were multiresistant. Main outcome measures: Protection of local existing vaccines to Streptococcus pneumoniae infections. Results: There were 14 different serotypes and most identified groups were 23, 19 and 6, 28,6% contained in the 7–valent vaccine, 42,9% in the 9-valent, 50% in the 11-valent and 71,4% in the 23-valent; 57,5% were resistant to penicillin and 30% to erythromycin. The invasive Streptococcus group proved to be more sensitive to antibiotics than the other groups; 19F and 23F serotypes were multiresistant. Conclusions: In our environment none of the studied vaccines protected all the infections caused by Streptococcus pneumoniae. Resistance to penicillin was high.